Blood pressure, hypertension and the risk of sudden cardiac death: a systematic review and meta-analysis of cohort studies - Pan, Han; Hibino, Makoto; Kobeissi, Elsa; Aune, Dagfinn (European journal of epidemiology, 2020)
Cardiovascular disease is the leading cause of death worldwide, while sudden cardiac death (SCD) accounts for over 60% of all cardiovascular deaths. Elevated blood pressure and hypertension have been associated with increased risk of SCD, but the findings have not been consistent. To clarify whether blood pressure or hypertension is associated with increased risk of SCD and to quantify the size and the shape of any association observed. PubMed and Embase databases were searched for published prospective studies on blood pressure or hypertension and SCD up to 30 April 2018. Summary relative risks (RRs) and 95% confidence intervals (CIs) were calculated using a random effects model. The meta-analysis included 2939 SCDs among 418,235 participants from 18 studies. The summary RRs were 2.10 (95% CI 1.71–2.58, I 2 = 56.7%, p heterogeneity = 0.018, n = 10) for prevalent hypertension, 1.28 (95% CI 1.19–1.38, I 2 = 45.5%, p heterogeneity = 0.07, n = 10) per 20 mmHg increment in systolic blood pressure (SBP) and 1.09 (95% CI 0.83–1.44, I 2 = 83.4%, p heterogeneity = 0.002, n = 3) per 10 mmHg increment in diastolic blood pressure (DBP). A nonlinear relationship was suggested between SBP and SCD. The results persisted in most subgroup and sensitivity analyses. There was no evidence of publication bias. This meta-analysis found an increased risk of SCD with hypertension diagnosis and increasing SBP. Future studies should clarify the association for DBP and the shape of the dose–response relationship between blood pressure and SCD.